Pengaruh problem solving terhadap kemandirian dan prestasi belajar matematika pada operasi bilangan bulat menggunakan metode kolom polamatika - Nurainun Nurainun; Cut Latifah Zahari (Mahesa Research Center, 2023)
This study aims to analyze the effect of the problem-solving model on independence and achievement in learning mathematics in the material of addition and subtraction of integers using the column pattern method for class VII students of SMP Taman Siswa Medan. This research is quantitative research, with an ex-post facto approach. The population used in this study were all grade VII students of SMP Taman Siswa Medan, with a purposive sampling technique used, so that the total sample was 41 respondents. Based on the research results, the average learning achievement score is 58. The mode value is 32, indicating that the acquisition value for the ability to understand with the greatest frequency is 32. The Problem-Solving Learning Model and independent learning simultaneously affect the mathematics learning achievement of class VII junior high school students by (R2 = 0.53) or 53%. The Problem-Solving Learning Model of students has a positive effect on the learning achievement of students in class VII junior high school mathematics. The independence of student learning has a positive effect on the mathematics achievement of class VII junior high school students.